The Effect of Hypertonic Mineral Solutions on Reparative-Regenerative Processes in a Skin Wound Defect in an Experiment - TsymbaliukV.І.; Strafun, S.S.; Bohdan, S.V.; Savosko, S.I. (TERRA ORTHOPAEDICA, 2023)
Background. Skin wound healing is a serious medical problem that is complicated by bacterial infections and requires appropriate care and treatment. Objective: to study the effect of a highly mineralized spray solution on the regenerative processes of the skin in a wound defect in an experiment. Materials and Methods. The study was conducted under laboratory conditions on 5 adult Chinchilla rabbits (weight 3.2-3.8 kg). A 10x10 cm area of skin on the back was shaved, and skin fragments measuring 2x2.5 cm were symmetrically excised on both sides of the spine at the level of X-XII ribs. A 0.5 ml solution of Staphylococcus aureus culture concentrate prepared in the laboratory of microbiology of the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine” was applied to the wounds. On the second and subsequent days of the experiment, a highly mineralized spray solution was applied to the experimental wound, while a physiological saline solution was applied to the control wound. On the 3rd and 7th days, a microbiological culture was taken from the wounds. After 7 days, the skin wound defect was taken for histological examination. Results. Macroscopically, there was a significant reduction in the area of the wound defect during the first three days of the experiment due to contraction, with a tendency to accelerate in the experimental defects. However, complete closure of the wound did not occur on the 7th day. The results of the cultures confirmed the growth of microbial colonies of Staphylococcus aureus, which visually (growth dynamics, number and size of colonies) did not differ from the biological samples obtained from control and experimental skin defects. Despite the contamination, purulent discharge from the wound was not observed. Conclusions. The experiment showed that the use of a highmineralized solution-based agent potentially contributes to regenerative processes in the skin, including angiogenesis and dermal restoration, but other effects, such as antiinflammatory and antibacterial, require further research.